Cassini CAPS‐ELS observations of negative ions in Titan's ionosphere: Trends of density with altitude. Issue 17 (5th September 2013) - Wellbrock, A.; Coates, A. J.; Jones, G. H.; Lewis, G. R.; Waite, J. H.
Abstract [1] Observations with the Electron Spectrometer sensor of the Cassini Plasma Spectrometer (CAPS‐ELS) have revealed the existence of negative ions in Titan's ionosphere. Negative ions are observed during encounters whenever the instrument points in the ram direction at altitudes 950–1400 km. Complex hydrocarbon and nitrile chemical processes are believed to take place which play a role in haze formation. The heaviest ions observed so far have masses up to 13, 800 amu/q. Using data from 34 Titan encounters, we show for the first time negative ion density trends of different mass groups, including total densities, with altitude. We determine peak densities and the associated altitudes at which they are observed and the highest altitudes at which individual mass groups are found.